Fatores de patogenicidade e estudo epidemiológico de Salmonella Minnesota de origem avícola - Resende, Adilson Ribeiro (2015)
Salmonellosis is an illness of global importance that worries health authorities by zoonotic potential and by being a barrier to international trade in food. Some serovars are directly associated with public health because they are incriminated in the etiology of the disease in humans, but others, like S. Minnesota, have brought concern the increase in the number of isolates in broiler production chain. Little is known about the virulence of this serovar and its potential to cause human disease. It aimed to evaluate virulence characteristics, antimicrobial resistance profile and the pattern of genetic similarity of 71 strains of S. Minnesota isolated in the production chain of broilers. The strains were isolated from 2009 to 2010 period, into two units of a company (A and B) with complete cycle of production, located in different states. Isolates were serotyped and submitted to antimicrobial susceptibility by disk diffusion test. Later, using PCR, were evaluated the presence of invA (invasion), lpfA (piliadhesion), agfA (pili-biofilm) and sefA (pili-adhesion) genes. Next, using PCR, was performed the identification of genes conferring resistance to beta-lactams (blaTEM, and blaSHV blaCTX-M). The phylogenetic relationship was determined by RAPD-PCR method. Among the drugs tested, the highest percentages of resistance were to tetracycline and sulfonamide, with 93.8% in unit A and 89.7% in unit B. Were recognized eight antimicrobial resistance profiles (A1 to A8) among strains isolated in industry, and 30 (93.8%) were resistant or intermediate resistance to at least one antibiotic. Sixteen (53.3%) were resistant to two antibiotics (A1) and 14 (46.7%) were considered multi resistant, because they were resistant to three or more classes of drugs (A2 to A7). Of the 39 strains from the B industry, 11 profiles have been identified (B1 to B11), being 35 (89.7%) resistant strains or with intermediate resistance to at least one drug. Of these, 10 (28.6%) were resistant to two antibiotics (B1), and 25 (71.4%) multiple resistant (B2 to B10). Of all strains of both industries, 100% were positive for the invA gene, 98.6% for agfA gene, 49.3% for lpfA gene and no strain showed the sefA gene. There was positivity of 52.1% for two genes simultaneously, and 47.9% for three of the evaluated genes. As to the resistance genes studied, only three strains (4,2%) were positive for blaTEM gene, 11 (15.5%) for blaCTX-M gene, and there was no positivity for blaSHV gene. Phylogenetic evaluation showed the presence of seven clusters with similarity greater than 80% and three distinct profiles. Based on the dendrogram we observed the spread with similar profiles in both companies, the feed as a possible source of contamination and the persistence of the agent for long periods in the environment. The presence of virulence genes and antimicrobial resistance profile observed in S. Minnesota strains demonstrate the need for constant monitoring in the poultry production chain to minimize end-product contamination hazards.